Legal and ethical issues in uses of stored tissue in human subjects research - Javitt, Gail (Henry Stewart Talks, 2015)
Human specimens and their increasing importance in scientific research, Rights, expectations, and obligations of tissue contributors, researchers and institutions, Legal cases and highly-publicized controversies, Policies to address ethical/legal concerns